Polynomials

Asked by hemant2020 | 9th May, 2010, 08:26: PM

Expert Answer:

Divident = (Divisor) (Quotient) + Remainder

 2x3 + x2 + x +1 = (Require polynomial)(-2x/3 + 1) + (4x +1) 

(Require polynomial)(-2x/3 + 1) = 2x3 + x2 + x +1 - (4x +1)

(Require polynomial)(-2x/3 + 1) = 2x3 + x2 -3 x 

(Require polynomial) = (2x3 + x2 -3 x)/(-2x/3 + 1)

(Require polynomial) = (6x3 + 3x2 -9 x)/(-2x + 3)

Regards,

Team,

TopperLearning.

Answered by  | 12th May, 2010, 07:03: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.